Surfactant effects in functionalized multiwall carbon nanotube-filled phase change materials - M. Arif Fikri, .; Pandey, A. K.; Rajamony, Reji Kumar; Sharma, Kamal; Kalidasan B., .; Mahendran, Samykano; Buddhi, D.; Tyagi, V. V. (Elsevier, 2024)
Energy storage using phase change materials (PCM) is an efficient way to harness thermal energy from solar energy due to its higher storage density, particularly for medium-temperature applications. However, the PCMs have lower thermal conductivity; owing to this, the thermal performance and heat transfer rate are inadequate. To address this challenge, the current work explores the integration of carbon-based nanoparticles into the PCM to enhance thermal conductivity and overall performance. In the present study, a novel functionalized multi-walled carbon nanotube (FMWCNT) dispersed in organic PCM in different weight fractions (0.1, 0.3, 0.5, 0.7 and 1.0 %) with and without surfactant is investigated. A two-step technique was employed to prepare nano enhanced phase change material (NePCM), with subsequent assessment of its thermophysical properties. Findings reveal a remarkable enhancement in thermal conductivity, with a staggering 150.7 % at 1.0 wt% FMWCNT without surfactant and a substantial 110.2 % improvement in the presence of surfactant. Furthermore, the Ultraviolet–visible spectrum (UV–Vis) demonstrates an 84.56 % reduction in transmittance compared to pure organic PCM. Furthermore, the prepared NePCM are thermally stable up to 405 °C and no chemical reaction takes place. Importantly, the best optimal nanocomposites chemical and thermal properties were evaluated for 500 heating and cooling cycles to ensure reliability. Remarkably, the inclusion of surfactant on FMWCNT enhanced PCM has minimal impact on thermophysical properties.